2009
DOI: 10.1007/s00251-009-0392-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct genetic control of parasite elimination, dissemination, and disease after Leishmania major infection

Abstract: Elimination of pathogens is the basis of host resistance to infections; however, relationship between persisting pathogens and disease has not been clarified. Leishmania major infection in mice is an important model of host-pathogen relationship. Infected BALB/c mice exhibit high parasite numbers in lymph nodes and spleens, and a chronic disease with skin lesions, splenomegaly, and hepatomegaly, increased serum IgE levels and cytokine imbalance. Although numerous gene loci affecting these disease symptoms have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 52 publications
3
40
0
Order By: Relevance
“…Experimental data have shown different sex influence on susceptibility to relatively closely related pathogen species [20, 21], different sex biases in susceptibility to the same Leishmania species in different host genotypes [21, 22], and different sex and genetic influence on organ-specific pathology [21, 23, 24]. For example, high resistance to skin lesions induced by L. mexicana was observed in females but not in males of DBA/2 mice, but the sex effect was opposite in L. major infection [20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental data have shown different sex influence on susceptibility to relatively closely related pathogen species [20, 21], different sex biases in susceptibility to the same Leishmania species in different host genotypes [21, 22], and different sex and genetic influence on organ-specific pathology [21, 23, 24]. For example, high resistance to skin lesions induced by L. mexicana was observed in females but not in males of DBA/2 mice, but the sex effect was opposite in L. major infection [20].…”
Section: Introductionmentioning
confidence: 99%
“…Genotype influence on sex differences was defined in the studies of L. major infection [22, 24]. Giannini [22] found no sex effect on L. major -induced skin pathology and mortality in BALB/cJ mice, but a higher susceptibility of B10.129(10M)ScSn females than males.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using mouse models have revealed functional heterogeneity of individual susceptibility genes, and indicate organ specific control of the antiparasite response [117,119,120]. Moreover, parasite elimination, as well as immunological and pathological processes, are under independent regulation [118]. A combination of recombinant mapping in combination with advanced tools of system genetics led to the identification of a potential candidate gene Fli1 (Friend leukemia integration 1) for Lmr2 [122], which uncovered a novel mechanism in the control of leishmaniasis.…”
Section: Mouse Models Of Infectious Diseases Uncover Novel Componentsmentioning
confidence: 99%
“…The most extensive information about the genetics of leishmaniasis in mouse models has been obtained with Leishmania major. These genetic studies have used several model systems, which include comparisons of two or more inbred strains [111][112][113], congenic strains [114,115], recombinant inbred strains [115] and recombinant congenic strains [116][117][118][119][120]. Genetic studies, especially those using recombinant congenic strains, led to a dissociation of correlated phenotypes, and showed that disease or healing in different strains occurs in association with different components of the immune response [121].…”
Section: Mouse Models Of Infectious Diseases Uncover Novel Componentsmentioning
confidence: 99%